Natural regeneration of Scots pine and Norway spruce close to the timberline in northern Finland - Juntunen, Vesa; Neuvonen, Seppo (Silva Fennica, 2006)
Two different datasets were analyzed in order to clarify the factors that affect regeneration success of Scots pine (Pinus sylvestris) and Norway spruce (Picea abies) in the climatically extreme areas in northern Finland. First, pine seed maturity and the number of cones in the trees were investigated at five pairs of study sites during the period 1997â2003. Secondly, the rate of seedling establishment and seedling survival of Scots pine and Norway spruce were monitored and compared among three different timberline zones (forest zone, timberline, tree line) in 13 localities during the period 1983â1999. The first study showed that both cone production (bud formation) and seed maturity may be limiting factors for successful reproduction in the climatically marginal habitats. Seed maturity correlated well with the temperature sum of the summer, but variation in the number of cones had a periodic component rather than strictly following the temperature sum of the summer of bud formation. Monitoring surveys since 1983 showed that pine and spruce regenerated more or less regularly in all the zones during 1983â1999. However, seedling mortality of pines was much higher compared to spruce. In general, initially small sized seedlings showed higher mortality compared with larger ones. The results suggest that besides restrictions in reproduction, stand dynamics in the timberline habitats are strongly controlled by seedling mortality due to a variety of causes.